2017
DOI: 10.1111/coa.12895
|View full text |Cite
|
Sign up to set email alerts
|

Current studies of immunotherapy in head and neck cancer

Abstract: Background: Recently, enormous progress in cancer therapy has been achieved by the use of immune checkpoint inhibitors. Activating the body's own immune system has added a novel and powerful therapeutic option for the treatment of melanoma and lung cancer. Furthermore, the potential use of immunotherapy is being extensively explored also in other malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 31 publications
0
44
0
2
Order By: Relevance
“…A lack of tumor volume data for example, even though clearly linked to LRC (81,(84)(85)(86), impedes the assessment of a role for or a bias from tumor volumes in such analyses. To minimize such treatment or tumor site related bias due to possible interactions; we deliberately excluded the biologically distinct oral cavity and HPV-positive oropharyngeal HNSCC (14,16,(87)(88)(89)(90) in our study. Our cohort also solely comprises definitive chemo-radiotherapytreated advanced HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of tumor volume data for example, even though clearly linked to LRC (81,(84)(85)(86), impedes the assessment of a role for or a bias from tumor volumes in such analyses. To minimize such treatment or tumor site related bias due to possible interactions; we deliberately excluded the biologically distinct oral cavity and HPV-positive oropharyngeal HNSCC (14,16,(87)(88)(89)(90) in our study. Our cohort also solely comprises definitive chemo-radiotherapytreated advanced HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of CTLA-4+ T reg cells in the HPV-positive HNSCC tumor microenvironment [107] and in the peripheral blood of advanced cervical cancer [108] patients, suggests a repressive role for CTLA-4 during HPV infection. The clinical benefits of blocking the CTLA-4 immune inhibitory pathway is also under clinical evaluation in cervical cancer [109] and HNSCC patients [110] .…”
Section: Chronic Hpv Infection Immunoregulatory Cytokine Milieu and mentioning
confidence: 99%
“…Pre-clinical studies have also demonstrated that the combination of HPV16 E7 DNA-based therapeutic vaccines with co-blockade of PD-1/PD-L1 signaling in E6- and E7-expressing transplantable TC-1 tumor bearing mice can significantly enhance the tumor -specific CTL response and improve tumor regression [134] , [135] , [136] . Currently, there are several clinical trials targeting blockade of PD-1/PD-L1 in HNSCCs and nivolumab (anti-PD1 antibody) has been approved by the FDA for the treatment of recurrent or metastatic HNSCC patients [110] , [137] . However, although pembrolizumab [138] and nivolumab [139] anti-PD-1 monoclonal antibodies are under phase I/II trials for the treatment of cervical and other anogenital cancers, it remains to be determined if these strategies can offer a therapeutic advantage for clearance of HPV-related tumors in patients.…”
Section: Chronic Hpv Infection Immunoregulatory Cytokine Milieu and mentioning
confidence: 99%
“…On the one hand, tumor infiltrating cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells eliminate the tumor cells and limit the tumor progression(Ferris, ). On the other hand, immunosuppressive cells, such as myeloid derived suppressor cells (MDSCs), tumor‐associated macrophages (TAMs), and regulatory T cells (Tregs), facilitate the tumor evasion and enhance the tumor progression(Dogan, Rieckmann, Munscher, & Busch, ). Based on the close relationship between immune status and HNSCC, immunotherapy has aroused extensive attention for HNSCC treatment.…”
Section: Introductionmentioning
confidence: 99%